Lack of Neuronal Glycogen Impairs Memory Formation and Learning-Dependent Synaptic Plasticity in Mice - Duran, Jordi; Gruart, Agnès; Varea, Olga; López-Soldado, Iliana; Delgado-García, José M.; Guinovart, Joan J. (Frontiers in Cellular Neuroscience, 2019)
Since brain glycogen is stored mainly in astrocytes, the role of this polysaccharide in neurons has been largely overlooked. To study the existence and relevance of an active neuronal glycogen metabolism in vivo, we generated a mouse model lacking glycogen synthase specifically in the Camk2a-expressing postnatal forebrain pyramidal neurons (GYS1Camk2a-KO), which include the prefrontal cortex and the CA3 and CA1 cell layers of the hippocampus. The latter are involved in memory and learning processes and participate in the hippocampal CA3-CA1 synapse, the function of which can be analyzed electrophysiologically. Long-term potentiation evoked in the hippocampal CA3-CA1 synapse was decreased in alert behaving GYS1Camk2a-KO mice. They also showed a significant deficiency in the acquisition of an instrumental learning task—a type of associative learning involving prefrontal and hippocampal circuits. Interestingly, GYS1Camk2a-KO animals did not show the greater susceptibility to hippocampal seizures and myoclonus observed in animals completely depleted of glycogen in the whole CNS. These results unequivocally demonstrate the presence of an active glycogen metabolism in neurons in vivo and reveal a key role of neuronal glycogen in the proper acquisition of new motor and cognitive abilities and in the changes in synaptic strength underlying such acquisition.